Personalize, participate, predict, and prevent: 4Ps in inflammatory bowel disease - Lenti, Marco Vincenzo; Scribano, Maria Lia; Biancone, Livia; Ciccocioppo, Rachele; Pugliese, Daniela; Pastorelli, Luca; Fiorino, Gionata; Savarino, Edoardo; Caprioli, Flavio Andrea; Ardizzone, Sandro; Fantini, Massimo Claudio; Tontini, Gian Eugenio; et al. (Frontiers in Medicine, 2023)
Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), is a complex, immune-mediated, disorder which leads to several gastrointestinal and systemic manifestations determining a poor quality of life, disability, and other negative health outcomes. Our knowledge of this condition has greatly improved over the last few decades, and a comprehensive management should take into account both biological (i.e., disease-related, patient-related) and non-biological (i.e., socioeconomic, cultural, environmental, behavioural) factors which contribute to the disease phenotype. From this point of view, the so called 4P medicine framework, including personalization, prediction, prevention, and participation could be useful for tailoring ad hoc interventions in IBD patients. In this review, we discuss the cutting-edge issues regarding personalization in special settings (i.e., pregnancy, oncology, infectious diseases), patient participation (i.e., how to communicate, disability, tackling stigma and resilience, quality of care), disease prediction (i.e., faecal markers, response to treatments), and prevention (i.e., dysplasia through endoscopy, infections through vaccinations, and post-surgical recurrence). Finally, we provide an outlook discussing the unmet needs for implementing this conceptual framework in clinical practice.